Awareness About Nanoparticle Based Dental Materials - N AKASH; GANESH S, DR. BALAJI; SOMASUNDARAM, DR. JAYALAKSHMI (The journal of contemporary issues in business and government, 2020)
Nanotechnology is the science and technology which brought revolution in the field of medical settings. The extreme small size allows for homogenous deposition leading to a longer future. The nanotech is based on the size of the object, that is less than 10−9. They are either spherical or irregular. Spherical is mostly used because they are extremely homogeneous, henceforth for a longer duration. This provides a working friendly environment. The aim of the study is to create awareness on nano technology in dental restorations. A questionnaire of 15 selective questions were made and circulated among dental students and practitioners. They were asked to fill in. The data was then collected and statistics were done using SPSS. The graphs were drawn and analyzed. The total 100 responses were taken, the data was analysed in SPSS by drawing graphs and piecharts. When comparing the awareness of nanoparticle based dental materials with gender, it was shown that females had a higher level of awareness when compared with males, but (p= 0.858), which was statistically insignificant. Most of the people were aware of nanoparticles and their applications. The reports concluded that the students and the dental practitioners are moderately aware of nanotechnology in dentistry.